PHRASEOLOGICAL UNITS IN UZBEK AND TURKISH: INVESTIGATING CULTURAL CODES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
Phraseological units constitute one of the richest and most culturally complex layers of language. They are not merely combinations of words but serve as vehicles reflecting the historical, cultural, social, and even psychological codes of a community. Each phraseological unit carries its own context, historical development, and semantic meaning, making language not only a tool for communication but also a mirror of culture and identity. Uzbek and Turkish belong to the Turkic language family and share many lexical and phraseological similarities. However, historical, geographical, and cultural differences have led to divergences in the context of use and semantic nuances of certain expressions. Comparative analysis of these units thus allows for a deeper understanding of the cultural and linguistic layers of both languages.